The effect of a proposed new strategy on developing approximate thinking among eleventh grade literature students Part of Master's Thesis - عارف, آ.م.د. کارزان محمد عارف; کریم, سارا واحد عمر کریم (Sulaimani Journal for Humanities, 2025)
The aim of this research is to examine the effectiveness of a proposed new strategy in developing critical thinking based on near transfer among 11th-grade humanities students, compared to the traditional method of instruction in the same subject, based on the following hypotheses: There is no statistically significant difference at the level of (0.05) between the mean scores of the pre-test and post-test in the development of critical thinking based on near transfer among the experimental group students who were taught using the proposed new strategy. There is no statistically significant difference at the level of (0.05) between the mean scores of the pre-test and post-test in the development of critical thinking based on near transfer among the control group students who were taught using the traditional method. There is no statistically significant difference at the level of (0.05) between the mean differences of both pre- and post-tests in the development of critical thinking based on near transfer between the experimental group (taught using the proposed new strategy) and the control group (taught using the traditional method).The researcher adopted an experimental method appropriate to the nature of the topic, objectives, and implementation steps of the research. The experimental design consisted of an experimental and a control group, each undergoing both pre-testing and post-testing — a design which helps in controlling the research variables.The research sample consisted of 11th-grade humanities students in public high schools in Sulaymaniyah city, under the administration of the west Education Directorate for the academic year (2024–2025). The research sample was intentionally selected from the 11th-grade humanities students of "Baker Jo Girls’ Preparatory School," totalling 26 students. They were equally divided into two groups after being matched on variables such as age, prior academic achievement, intelligence, and previous performance in history. Then, randomly, two groups were formed: one experimental group taught using the near transfer-based strategy, and one control group taught through the traditional method. The researcher developed a critical thinking near transfer scale consisting of 30 multiple-choice items. The scale was later validated by experts with a reliability score of 92%. The researcher also conducted a re-testing procedure on a separate group of 50 students at two different times, obtaining a stability coefficient of 0.84. The statistical tools used in the study were the t-test and Pearson correlation coefficient. The researcher concluded that there was a statistically significant difference between the experimental and control groups in favour of the experimental group in terms of the development of critical thinking based on near transfer.
Keywords: Effectiveness; Proposed New Strategy; Near Transfer Thinking; History; 11thGrade Humanities Students